2013
DOI: 10.1016/j.powtec.2013.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbide powder characteristics on the PVT behavior of powder injection molding compounds

Abstract: Effect of powder concentration and particle size distribution of highly filled cemented carbide compounds on their pressure-volume-temperature (PVT) characteristics and thermal properties was investigated. PVT data of compounds containing up to 50 vol.% of powder evaluated on a high-pressure mercury dilatometer reveals that the pressure influences both detected phase transitions, but it causes a different effect on the melting and crystallization of the material only for the higher transition (corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…1,25,26 On the contrary, the quality was poor when the particle density was higher than 9 g cm 23 and the particle size bigger than 15 mm. 3,13 We also noticed that the green body prepared with the spherical powders owned the better homogeneity, even the particle sizes were big. 1,5,25 The homogeneity of green bodies prepared with plate-like powders was poor, and defect formation in debinding and sintering was related to the particles, even the particle sizes were small.…”
Section: Verificationmentioning
confidence: 85%
See 3 more Smart Citations
“…1,25,26 On the contrary, the quality was poor when the particle density was higher than 9 g cm 23 and the particle size bigger than 15 mm. 3,13 We also noticed that the green body prepared with the spherical powders owned the better homogeneity, even the particle sizes were big. 1,5,25 The homogeneity of green bodies prepared with plate-like powders was poor, and defect formation in debinding and sintering was related to the particles, even the particle sizes were small.…”
Section: Verificationmentioning
confidence: 85%
“…3 Hausnerova et al 3 investigated the morphology of moulded samples by atomic force microscopy, and found that the samples with large particle dimensions or particle densities had less homogenous microstructure. Shivashankar et al 4 used the torgue rheometer to investigate the powder-binder separation phenomena of several feedstocks, and the results confirmed that high powder loading, irregular particle shape or small particle size increased powderbinder separation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations